Biosimilars: mechanisms of action, clinical efficacy and therapeutic implications - Sadikan, Muhammad Zulfiqah; Ahmad Hairi, Haryati; Mohmad Sabere, Awis Sukarni (MNNF Publisher, 2024)
Biosimilars have been defined as agents used to deliver biopharmaceuticals that are chemically, functionally, and therapeutically equivalent to approved reference biologics. These biological agents are derived from living organisms or cells, and comparability tests are carried out to assess whether they can function in the same way as the corresponding reference products. The future of healthcare as a result of biologic-based therapies has a high potential for transforming health systems, making them more accessible and affordable. Therefore, biosimilars as a part of the improved healthcare delivery systems will be extremely beneficial in the future. In the current chapter, the author delves into how biosimilars work and other aspects that distinguish them from reference products. It also assesses biosimilar safety and efficacy in real-world clinical situations by comparing therapeutic properties to the initial reference biologic. Furthermore, this chapter analyses the potential protective benefits and risks of biosimilars upon systematic application, presenting a concise viewpoint for current and future healthcare advancements. By considering these issues, this chapter covers different aspects of biosimilars' impact on both patients and healthcare systems.